Kaitan Jumlah Wisatawan Terhadap Pendapatan Asli Daerah Provinsi DKI Jakarta Tahun 2009 – 2013 - Sihotang, Yeppy; Santoso, Hendra F.; Iskandar, Denny (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2015)
Revenue (PAD) is a local earned income levied by local regulations in accordance with the legislation. Revenue PAD aims to give authority to local governments to fund the implementation of regional autonomy in accordance with the potential Q ( the region as the embodiment of decentralization)n. Travelers are people who travel without traveling temporarily while sightseeing and fun solely to enjoy recreational activities (use of free time to rest, relax and have fun to do reverse and improve fitness and physical and mental health as a result and work activities daily) or to meet the diverse desires. This study aims to determine the number of domestic tourists and foreign. tourists are concerned with local revenues Jakarta. The method used in this research is descriptive analysis. The study uses data reports revenue budget and actual data of the area and tourists Jakarta. Then the results obtained that the number of tourists visiting jakarta has relation to revenue (PAD). Keyword : Number Of Tourist, Local Earned Income